Body Image Dissatisfaction and Hormonal Therapy Effects in Indonesian Females with Turner Syndrome - Dinda Tiara Firdaus; Annastasia Ediati; Achmad Zulfa Juniarto (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Turner Syndrome (TS) is a genetic disorder that impairs the development of secondary sexual characteristics and may negatively affect body image. Hormonal therapy is administered to stimulate puberty, but its impact on body image remains inconclusive. Data from Indonesia is still limited. This study aims to analyze the differences in body image assessment between females with and without TS, and to evaluate the relationship between the duration of hormonal therapy and body image perception in females with TS. Methods: A cross-sectional case-control study was conducted at CEBIOR, Faculty of Medicine, Diponegoro University. Twenty-eight females with TS, aged 14-31 years, participated. Body image was assessed using a validated questionnaire, and secondary sexual characteristics were evaluated using the Tanner stage. Data were analyzed using the Mann-Whitney U test and Spearman's correlation. Results: The mean Tanner stage was increased from 3.6 ± 1.1 to 6.2 ± 2.7 after hormonal therapy. No significant difference in overall body image dissatisfaction was found between females with TS and controls (MdnTS = 74.5 [34–120]; MdnC = 68.0 [31–109]; p = 0.512). However, females with TS showed significantly higher dissatisfaction scores in the sexual domain (MdnTS = 11 [4–20]; MdnC = 7.5 [4–16]; p = 0.013) and in height–weight perception (MdnTS = 7 [3–10]; MdnC = 6 [2–8]; p = 0.014). No significant correlation was found between therapy duration and body image scores, although a weak negative trend was observed for height–weight perception (r = –0.373; p = 0.051). Conclusion: Hormonal therapy increased Tanner stage but did not reduce overall body image dissatisfaction. Females with TS reported greater dissatisfaction in specific domains. These findings suggest that psychosocial interventions are crucial for enhancing body image and overall well-being in this population.